Value of serum glucose-6-phosphate isomerase in patients with rheumatoid arthritis and correlation with disease activity: A case-control study - Neda Soleimani; Masoud Hosseinzadeh; Zahra Habibagahi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Rheumatoid arthritis (RA) is a common multisystemic autoimmune disease with peripheral joint involvement. Many autoantibodies have been introduced in the course of RA; some of them have diagnostic and prognostic value. In this study, our aim is to determine the value of serum glucose-6-phosphate isomerase (G6PI) antigen (Ag) as a diagnostic and prognostic marker in RA. MATERIALS AND METHODS: Eighty-seven known cases of RA who referred to an outpatient clinic of Shiraz University of Medical Sciences and 76 healthy controls were selected. Serum G6PI Ag was measured using sandwich enzyme-linked immunosorbent assay method, and the enzyme level was compared in the patient and control group, we also compared the enzyme level of patient group with disease activity, disease duration, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF), and anti-cyclic citrullinated peptide (anti-CCP) antibody (Ab). The data were analyzed using SPSS V 16 software. RESULTS: Positivity for G6PI was detected in 34.5% (30/87) of RA patients and 9.2% (7/76) of control group (P < 0.001). There was no significant correlation between enzyme level and disease activity, disease duration, ESR, CRP, RF, and anti-CCP Ab. CONCLUSIONS: Overall, in our study, although there was a significant difference in serum G6PI Ag between patient and control group, no significant correlation was detected between serum G6PI level and disease activity score, ESR, CRP, and anti-CCP Ab, but relative correlation with ESR and disease duration could be challenging. G6PI Ag could be introduced as a diagnostic marker in RA, but its role as a prognostic marker is controversial.